2003
DOI: 10.1088/0953-8984/15/6/324
|View full text |Cite
|
Sign up to set email alerts
|

In situoptical absorption spectroscopy of annealing behaviours of quench-deposited films in the binary system CsI  PbI2

Abstract: We have investigated annealing behaviours of quench-deposited films of the binary CsI-PbI 2 system by in situ optical absorption spectroscopy. Various films composed of multiple crystalline phases of CsPbI 3 and/or Cs 4 PbI 6 as well as of CsI and/or PbI 2 are obtained, depending on the mixing ratio of the CsI and PbI 2 . It is difficult to prepare films purely composed of a single CsPbI 3 or Cs 4 PbI 6 phase alone. However, it is possible to obtain films where crystallites of either CsPbI 3 or Cs 4 PbI 6 coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
3
9
0
3
Order By: Relevance
“…Смесь порошков предварительно расплавлялась под экраном, помещенным между испа-рителем и подложкой, затем расплав испарялся на под-ложку. Температуру подложки варьировали от 373 до 403 К. При температуре подложки T sub = 393 К полу-чаются монофазные пленки RbPbI 3 с характерным для этого соединения спектром, подобным спектру CsPbI 3 [7][8][9], с интенсивной длинноволновой А I -полосой при 2,975 эВ (90 К) на краю поглощения. В спектре тонких пленок, полученных при более низкой температуре подложки T sub ≈ 353 К, кроме А I -полосы, присущей RbPbI 3 , появляется более высокочастотная А II -полоса, соответствующая, по-видимому, второму тройному со-единению (рис.…”
Section: экспериментunclassified
See 2 more Smart Citations
“…Смесь порошков предварительно расплавлялась под экраном, помещенным между испа-рителем и подложкой, затем расплав испарялся на под-ложку. Температуру подложки варьировали от 373 до 403 К. При температуре подложки T sub = 393 К полу-чаются монофазные пленки RbPbI 3 с характерным для этого соединения спектром, подобным спектру CsPbI 3 [7][8][9], с интенсивной длинноволновой А I -полосой при 2,975 эВ (90 К) на краю поглощения. В спектре тонких пленок, полученных при более низкой температуре подложки T sub ≈ 353 К, кроме А I -полосы, присущей RbPbI 3 , появляется более высокочастотная А II -полоса, соответствующая, по-видимому, второму тройному со-единению (рис.…”
Section: экспериментunclassified
“…1, кривая 1). Аналогичная ситуация на-блюдалась для соединений системы CsI-PbI 2 [6][7][8][9], в которой при низких температурах подложки (T sub ≤ ≤ 353 К) получались двухфазные пленки (рис. 1, кри-вая 3), которые после отжига в течение несколь-ких часов при температуре свыше 400 К переходили в монофазные со спектром, характерным для Cs 4 PbI 6 (рис.…”
Section: экспериментunclassified
See 1 more Smart Citation
“…This band was attributed to the Cs 4 PbI 6 compound in [9], and it was concluded that CsPbI 3 is unstable in the gas phase and decomposes to form Cs 4 PbI 6 . The results of [7,9] encouraged Japa nese physicists [10,11] to develop methods for prepar ing pure CsPbI 3 and Cs 4 PbI 6 phases to measure their absorption spectra. Kondo et al [10,11] proposed to deposit successively thin CsI and PbI 2 layers of a cer tain thickness on a transparent substrate cooled to 77 K. The ratio of the thicknesses of the two layers was chosen according to the molar composition of the desired compound.…”
mentioning
confidence: 99%
“…phase of the compounds, the solid-state chemical reaction allows to disperse crystallites of these compounds separately in the CsIcrystal environment. Generally the products of solid-state chemical reaction have better crystallinity for film-crystal interfaces (such as the PbI 2 -CsI interface of the PbI 2 /CsI system mentioned above, and the CuCl-KBr interface of a CuCl/KBr system described in Section 5) than for film-film interfaces (such as the PbI 2 -CsI interface of a PbI 2 /CsI/silica-glass system [47], i.e., a system of PbI 2 film on CsI film on silica-glass substrate, and the CuCl-KBr interface of a CuCl/KBr/Al 2 O 3 system described in Section 6). In what follows, dramatic improvement of CuBr excitonic PL recently achieved [61][62][63][64] for the film-crystal interface systems is systematically overviewed including brief descriptions of further developments achieved afterwards.…”
mentioning
confidence: 99%